The Effect of Giving Bokashi Lamtoro (Leucaena leucocephala L.) on The Growth of Liberica Coffee Seedlings (Coffea liberica W. Bull ex Hiern) in The Nursery - Muhammad Abel Rovillo Dewa; Anis Tatik Maryani; Nyimas Myrna Elsa Fathia; Bambang Niko Pasla (Jurnal Prajaiswara, 2026)
Introduction/Main Objectives: Liberica coffee (Coffea liberica W. Bull ex Hiern) is one of the leading commodities in Jambi Province, but its productivity tends to decline due to low seed quality, less fertile planting media, and suboptimal fertilization. One effort to improve seed quality is through the use of organic fertilizer bokashi lamtoro (Leucaena leucocephala L.). This study aims to determine the effect of bokashi lamtoro on the growth of Liberica coffee seedlings in nurseries and determine the best dose that provides optimal growth. Research Methods: The study was conducted in June–August 2025 at the Teaching and Research Farm, Faculty of Agriculture, University of Jambi using a Completely Randomized Design (CRD) with five treatments and four replications. The treatments consisted of P0 (no bokashi + 100% inorganic fertilizer), P1 (100 g bokashi + 50% inorganic fertilizer), P2 (150 g bokashi + 50% inorganic fertilizer), P3 (200 g bokashi + 50% inorganic fertilizer), and P4 (250 g bokashi + 50% inorganic fertilizer). Finding/Results: The results showed that Treatment P4 produced the highest values for most growth parameters. However, in terms of efficiency, the dose of 200 g bokashi leucaena (lamtoro) + 50% inorganic fertilizer was considered the best dose because it was able to produce optimal seedling growth with more efficient bokashi use. Conclusion: It can be concluded that bokashi leucaena is effective in increasing the growth of Liberica coffee seedlings during the seedling phase.